In defense of shame the faces of an emotion - Deonna, Julien A.; Rodogno, Raffaele; Teroni, Fabrice (New York : Oxford University Press, 2011)
Is shame social? Is it superficial? Is it a morally problematic emotion? In this book, Julien Deonna, Raffaele Rodogno, and Fabrice Teroni propose an original philosophical account of shame aimed at answering these questions.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references and index.
Keywords: Shame